The Effects of Competency, Work Placement, and Career Development on Job Performance: Lessons From Public Sector in An Emerging Country - Afriana, Afriana (Jurnal Manajemen, 2021)
This research aimed to figure out the effects of competency, work placement, and career development on government officers' performance. This research used a descriptive-quantitative research design with a questionnaire as an instrument. The purposive sampling technique was used to extract a sample, which consisted of 250 respondents who were government officers from 26 local government agencies in the Yapen Islands Regency. This research employed a multiple regression analysis as the data analysis technique with SPSS version 25. The research results show that the variables competency and career development had significant positive effects on employee performance. In contrast, the variable work placement did not have any effect on employee performance.